The Influence of Transformational Leadership, School Culture, and Job Satisfaction on Teacher Performance in Public Elementary Schools of Temanggung District - Anita Yuli Astuti; Ngasbun Egar; Ghufron Abdullah (SOSIOEDUKASI, 2025)
This study investigates the influence of transformational leadership, school culture, and job satisfaction on teacher performance in public elementary schools in Temanggung District. Employing a quantitative research approach with a survey method, data were collected from 152 teachers using validated questionnaires and analyzed with multiple regression techniques. The findings reveal that transformational leadership contributes the highest impact on teacher performance (48.7%), followed by job satisfaction (38.7%) and school culture (37.4%). Simultaneously, these three variables account for 61.6% of the variance in teacher performance, indicating that the combination of effective leadership, positive school culture, and high job satisfaction significantly enhances teacher performance. The novelty of this research lies in its integrative model that simultaneously examines the roles of leadership, organizational culture, and job satisfaction in the context of Indonesian elementary education, particularly in Temanggung. However, this study is limited to a single district and focuses only on three independent variables. Future research should expand the scope to other regions and incorporate additional variables such as pedagogical competence, intrinsic motivation, and organizational commitment, possibly employing a mixed-methods approach. These extensions will provide deeper insights and more comprehensive recommendations for improving teacher performance and educational quality.